63rd EAGE Conference &Amp; Exhibition 2001
DOI: 10.3997/2214-4609-pdb.15.o-20
|View full text |Cite
|
Sign up to set email alerts
|

Faeroe Sub-Basalt Seismic Imaging - a New Iterative Time Processing Approach

Abstract: Converted wave terminologyConversion occurs each time a wave impinges at non-normal incidence on an impedance contrast, and is accompanied by a partition of energy between different wave types (P, S, reflected, transmitted). Some of the possible conversions have such a low energy content that they can be considered negligible for seismic imaging purposes. Moreover, marine acquisition with a towed streamer requires that a P wave must arrive at the receiver. Among the many different types of waves analysed, some… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2003
2003
2008
2008

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 4 publications
0
5
0
Order By: Relevance
“…Once V stac^ has been determined during pre-processing, the pre-processed subsets are migrated several times, using conventional Kirchhoff PSTM (e.g. Robein & Hanitzsch, 2001) for major wave types identified during pre-processing, as outlined by Barzaghi et al (2002). We begin with a smooth 2D model for which we search the principal reflections after PSTM has been applied with the velocity V m i g = V s t a ck-This leads in general to non-flat image gathers and requires additional (e.g.…”
Section: Prestack Migration and Velocity Updatingmentioning
confidence: 99%
See 2 more Smart Citations
“…Once V stac^ has been determined during pre-processing, the pre-processed subsets are migrated several times, using conventional Kirchhoff PSTM (e.g. Robein & Hanitzsch, 2001) for major wave types identified during pre-processing, as outlined by Barzaghi et al (2002). We begin with a smooth 2D model for which we search the principal reflections after PSTM has been applied with the velocity V m i g = V s t a ck-This leads in general to non-flat image gathers and requires additional (e.g.…”
Section: Prestack Migration and Velocity Updatingmentioning
confidence: 99%
“…According to the elastic migration principle (Kuo & Dai, 1984), we migrated data using a combination of velocities and event enhancement amplitude weights suitable for each event. This makes it possible to avoid misprocessing and misinterpreting non-PP arrivals as primary PP reflections, without applying labourintensive pre-processing that involves the use of handpicked mutes or interactive interpretations based on calculations of the traveltime response (Barzaghi et al, 2002;Van der Baan et al, 2003). In event-based migration with accurate velocities, migrated energy from assumed wave-propagation modes coincides with the actual reflector, although different parts of this reflector are imaged with each event (Kuo & Dai, 1984).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The large impedance contrast between basalt and the surrounding sediments also generates strong converted waves (Purnell, 1992). These waves may contain more energy than the standard PP reflections, especially at long offsets (Barzaghi et al (2002). Hence, the challenge of multi-mode data preprocessing is to separate various wave modes associated with high impedance contrast interfaces and to remove unwanted arrivals such as water peg-leg multiples and converted PS waves from TB that often interfere with target reflections.…”
Section: Introductionmentioning
confidence: 99%
“…Recent investigations have shown that wide-angle acquisition (e.g., Fliedner and White, 2001;Fruehn et al, 2001) combined with a broad-band, low-frequency source (White et al, 2002) has the potential to overcome some of the aforementioned difficulties. Further, development of processing techniques based on modeling (e.g., Hansen et al, 2001) and converted wave energy (e.g., Barzaghi et al, 2002) enhances our ability to extract sub-basalt information from seismic reflection data.…”
Section: Introductionmentioning
confidence: 99%